Natural Products: Experimental Approaches to Elucidate Disposition Mechanisms and Predict Pharmacokinetic Drug Interactions - Paine, Mary F. (Drug Metab Dispos, 2020)
Natural products have been used by humans since antiquity for both egregious and beneficial purposes. Regarding the latter, these products have long been valued as a rich source of phytochemicals and developed into numerous life-saving pharmaceutical agents. Today, the sales and use of natural products with purported medicinal qualities continue to increase worldwide. However, natural products are not subject to the same premarket testing requirements as pharmaceutical agents, creating critical gaps in scientific knowledge about their optimal use. In addition, due to the common misperception that “natural” means “safe,” patients may supplement or replace their prescription medications with natural products, placing themselves at undue risk for subefficacious pharmacotherapy or potentially toxic exposure. Collectively, with few exceptions, researchers, health care providers, and educators lack definitive information about how to inform consumers, patients, and students in the health professions on the safe and optimal use of these products. Recognition of this deficiency by key stakeholders, including the three pillars of biomedical research—industry, academia, and government—has facilitated multiple collaborations that are actively addressing this fundamental knowledge gap. This special issue contains a collection of articles highlighting the challenges faced by researchers in the field and the use of various experimental systems and methods to improve the mechanistic understanding of the disposition and drug interaction potential of natural products. Continued refinement of existing, and development of new, approaches will progress toward the common overarching goal of improving public health. SIGNIFICANCE STATEMENT: Natural products with purported medicinal value constitute an increasing share of the contemporary health care market. Natural products are not subject to the same premarket testing requirements as drug products, creating fundamental scientific knowledge gaps about the safe and effective use of these products. Collaborations among industrial, academic, and governmental researchers in multiple disciplines are anticipated to provide the definitive information needed to fill these gaps and improve public health.